Effects of Simulation on Students Achievement, Retention, and Skill Performance in Motor Vehicle Mechanic in Niger State, Nigeria - Aliyu Mustapha; Robert Ogbanje Okwori; Abdullahi Abubakar Kutiriko; Abdullahi Raji Egigogo (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
Traditional teaching methods, such as lectures, have long been criticized for their lack of innovation and passive learning approach, particularly in technical disciplines like Motor Vehicle Mechanics (MVM). This study explores the impact of simulation-based instruction, using the Motor Vehicle Mechanic Computer Animation Instructional Package (MVMCAIP), compared to conventional methods in enhancing students' achievement, retention, and skill performance. Employing a quasi-experimental and descriptive multi-method design, the research was conducted across technical colleges in Niger State, involving 118 Technical College II students. Of these, 58 students were taught using MVMCAIP, while 60 received traditional instruction. Data collection tools included the Motor Vehicle Mechanic Achievement Retention Test (MVMART), the Motor Vehicle Mechanic Skill Performance Test (MVMSPT), and lesson plans. Findings reveal that simulation-based instruction significantly enhances student performance across all metrics, with gender influencing achievement scores but showing no significant interaction effect with instructional methods. These results highlight the potential of simulation tools to revolutionize technical education by providing interactive, engaging, and effective learning experiences. The study recommends integrating simulation technologies like MVMCAIP into MVM curricula and prioritizing professional development programs to enhance educators’ proficiency with these tools, paving the way for more impactful and future-ready technical education.